KAJIAN YURIDIS MEDIASI PENAL DALAM PENANGANAN PERKARA TINDAK PIDANA PERBANKAN DI TINGKAT PENYIDIKAN - Agus Hartanto; Gunarto Gunarto (UNISSULA Semarang, 2017)
In this research the problem will be discussed is the implementation of Penal Mediation in handling Banking crime and weaknesses and solution of Penal Mediation implementation in handling Banking crime at investigation level.This research uses empirical juridical approach method. Empirical juridical is a procedure used to solve problems by researching secondary data first and then followed by researching primary data field or the community.The conclusions of this study are the extent of the field of study that must be explored in relation to the prevention and mitigation of criminal acts, but the prevention and mitigation of criminal acts, is in fact an inseparable link. Preventive action is expected to minimize the possibility of Criminal Acts in the banking sector, while although the prevention of banking crime through the operation of criminal law is intended to impose a defendant against the perpetrator, and provide protection from the criminal community, but on the other hand also has an adressat to provide deterent effect to prevent others from doing the same deeds as disguised in banking laws and other related laws. Keywords: Penal Mediation, Crime, Banking, Investigation